Attracting Capital for Railway Development in China - Lawrence, Martha; Ollivier, Gerald (World Bank, Washington, DC, 2016)
China Railways Corporation (CRC) is considering new ways to attract capital to support the strategic development of the railway sector. Currently, government is the predominant equity financier, with debt being supplied by domestic bank credits and limited amounts borrowed from International Financial Institutions such as the World Bank and Asian Development Bank. Considering its high level of accumulated debt and liabilities (RMB 3.7 trillion on an asset base of 5.7 trillion), CRC wishes to explore equity investment mechanisms, to increase cash flow from its core and non-core activities, and to use different financing channels as a way to leverage the value of its assets and introduce market-based business models to the sector. CRC is seeking to attract investment from both the private sector and from public sources such as local governments and state owned enterprises. It refers to these sources of capital as ‘social capital.’ This report examines how companies in China and railways in seven other countries, China, France, India, Japan, Poland, Russia, United Kingdom, United States, have attracted capital and made capital budgeting decisions to support their strategic development.